2019
DOI: 10.1002/etc.4593
|View full text |Cite
|
Sign up to set email alerts
|

Full–Life Cycle Toxicity Assessment of Sediment‐Bound DDT and Its Degradation Products on Chironomus dilutus

Abstract: Because of its hydrophobicity and persistence, dichlorodiphenyltrichloroethane (DDT) is ubiquitous in sediments and poses significant risk to benthic organisms. Therefore, it is imperative to evaluate the long‐term toxicity of DDT. However, limited information is available on its chronic toxicity to benthic invertebrates. Full–life cycle toxicity of sediment‐bound DDT to Chironomus dilutus was assessed. Median lethal concentrations (with 95% confidence limits) of DDT and its degradation products (DDX) to C. di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Sediment toxicity was assessed by determining adverse effects to the chironomid emergence process (time and rate) following the standard protocols with minor modifications. ,, Briefly, 20 first-instar chironomid larvae (5 days after hatching) were added into the sediments on day 0 and their emergence process was monitored over the course of the experiment. They were fed daily by adding crushed fish food directly into the chamber (20 mg day –1 for days 1–10 and then 40 mg day –1 for days 11–21).…”
Section: Methodsmentioning
confidence: 99%
“…Sediment toxicity was assessed by determining adverse effects to the chironomid emergence process (time and rate) following the standard protocols with minor modifications. ,, Briefly, 20 first-instar chironomid larvae (5 days after hatching) were added into the sediments on day 0 and their emergence process was monitored over the course of the experiment. They were fed daily by adding crushed fish food directly into the chamber (20 mg day –1 for days 1–10 and then 40 mg day –1 for days 11–21).…”
Section: Methodsmentioning
confidence: 99%
“…The approach identified a limited number of contributors (acidic pH, sulfate, and Cu) to toxicity, but the added use of toxicity identification evaluations revealed acidic pH as the main cause. Ma, Li, Li, and You (2019) evaluated the toxicity of DDT in sediment to the benthic invertebrate Chironomus dilutus . They observed that the main contributor of toxicity to C. dilutus was not the DDT but a degradation product dichlorodiphenyldichloroethane (DDD) that was produced over time.…”
Section: Assessmentmentioning
confidence: 99%
“…According to published literature, these organisms may be sensitive to DDT, Hg, and As. DDT exposure is known to affect Chironomus emergence, mortality, reproduction, growth, and sex ratio [ 24 , 25 ]. Exposure to Chironomus riparius to Hg has been reported to reduce growth and emergence, delay development time, and decrease activity of the larvae [ 10 ], and increase morphological deformities [ 26 ].…”
Section: Introductionmentioning
confidence: 99%